Konseling Komunitas Urban: Analisis Teoritis dan Implementasi dalam Konteks Kehidupan Perkotaan - Ikram Riski; Tiara Fitya Alfarizqa Putri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Rapid urbanization in Indonesia has created various psychosocial challenges, including stress, family conflict, social alienation, and socioeconomic disparities. These conditions require counseling services that extend beyond individual interventions toward community-based approaches that address the broader social impacts of urban life. This study aims to analyze the concepts, principles, and implementation strategies of urban community counseling as an approach to strengthening psychosocial well-being in urban populations. Using a literature review method, this study synthesizes scholarly books, journal articles, and empirical research related to community counseling and contemporary urban issues. The findings indicate that urban community counseling is effective in enhancing community resilience through participatory, empowerment-based, multicultural-sensitive, and cross-sector collaborative approaches. Programs such as family counseling, youth mentoring, support for vulnerable groups, and the integration of digital counseling services have been shown to improve social connectedness and mental health outcomes. This study affirms that urban community counseling plays a strategic role in promoting mental health development and reinforcing social cohesion in the context of modern urbanization.